Role of Gsα in Central Regulation of Energy and Glucose Metabolism - Weinstein, L. S. (Hormone and Metabolic Research, 2014)
GNAS is a complex imprinted locus with multiple oppositely imprinted gene products, including the G protein α-subunit Gsα that is expressed primarily from the maternal allele in some tissues and the Gsα isoform XLαs that is expressed only from the paternal allele. Maternal Gsα mutations in mice and in patients with Albright hereditary osteodystrophy lead to obesity, insulin resistance, and hyperlipidemia. Studies in mice show that these effects are primarily due to Gsα imprinting in the central nervous system and that Gsα deficiency in one or more regions of the central nervous system lead to reduced sympathetic nervous system and energy expenditure without affecting food intake. Loss of Gsα in the central nervous system appears to lead to these effects primarily through impairment of melanocortin signaling. Loss of XLαs in mice leads to opposite effects on energy and glucose metabolism.
Keywords: genomic imprinting; obesity; pseudohypoparathyroidism; Albright hereditary osteodystrophy